The relevance of basic psychological needs and subject interest as explanatory variables for student dropout in higher education — a German case study using the example of a cooperative education program - Wild, Steffen; Rahn, Sebastian; Meyer, Thomas (European journal of psychology of education, 2023)
Student dropout in higher education is a challenge for higher education systems. In recent years, there has been an increasing focus on analyzing motivational aspects in order to counteract dropout. However, the detailed impact mechanisms and processes of motivation on dropout have not been sufficiently researched. For example, there is very little research analyzing the preconditions of motivation and their influence on motivation as well as their eventual influence on dropout. From the background of self-determination theory and the person-object theory of interest, this study analyzes the effects of satisfying the three basic psychological needs on dropout via subject interest. We use data from a cross-sectional design with N = 2662 cooperative students in their first academic year. Our analysis identifies a direct effect of relatedness and subject interest on dropout. Furthermore, indirect effects of satisfying basic psychological needs, specifically, autonomy and relatedness, on dropout via subject interest are noted. We evaluate our results in the context of the current state of research and discuss implications.